A diverse landscape of FGFR alterations and co-mutations suggests potential therapeutic strategies in pediatric low-grade gliomas - April A. Apfelbaum; Eric Morin; Dominik Sturm; Georges Ayoub; Jeromy DiGiacomo; Sher Bahadur; Bhavyaa Chandarana; Phoebe C. Power; Margaret M. Cusick; Dana Novikov; Prem Prabhakar; Robert E. Jones; et al. (Nature Communications)
Abstract Oncogenic alterations in fibroblast growth factor receptor (FGFR)-family proteins occur across cancers, including pediatric gliomas. Our genomic analysis of 11,635 gliomas across ages finds that 5.3% of all gliomas harbor FGFR alterations, with an incidence of almost 9% in pediatric gliomas. Alterations in FGFR proteins are differentially enriched by age, tumor grade, and histology, with FGFR1 alterations associated with glioneuronal histologies. Leveraging isogenic systems, we confirm FGFR1 alterations to induce downstream Mitogen Activated Protein Kinase (MAPK) and mTOR signaling pathways, drive gliomagenesis, activate neuronal transcriptional programs and exhibit sensitivity to MAPK pathway and pan-FGFR inhibitors. Finally, we perform a retrospective analysis of clinical responses in children diagnosed with FGFR-altered gliomas and find that treatment with currently available inhibitors is largely associated with stability of disease. This study provides key insights into the biology of FGFR1-altered gliomas, therapeutic strategies to target them and associated challenges that still need to be overcome.